FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS PELAYANAN PUBLIK PADA ERA NEW NORMAL DI KANTOR KELURAHAN KLABULU DISTRIK MALAIMSIMSA KOTA SORONG - Abraham Yedutun Calvin Numberi; Ratna Rosmauli Pakpahan; Susana Magdalena Welly Muskita; Arce Yulita Ferdinandus (JURNAL BADATI, 2023)
This study aims to determine the policy of the public service system to achieve the quality of public services and the factors of the gap in the quality of public services in the new normal era at the Klabulu Village Office, Malaimsimsa District, Sorong City. The results of the study concluded that policy changes were carried out for good reasons, took their own steps, the changes were planned and not drastic or sudden, but their implementation was immediately adjusted to the announcement of the Sorong City Government and/or the Sorong City Covid-19 Task Force regarding the allowed working hours for agencies. government. All service officers/employees affected by the change are involved in planning the change. The Klabulu Village Government, Malaimsimsa District, Sorong City, in adapting to pandemic conditions, has made adjustments to the work system by carrying out health protocols in daily activities and carrying out official duties in the office (work from office / WFO) with the support of human resources. Performance of Government Agencies (Lkjip), tiered internal supervision and performance evaluation of implementers, and service employees are disciplined; infrastructure support with the availability of facilities and infrastructure for adjusting health protocols.